The impact of crises on investments and financing of Brazilian companies: an approach in the context of financial constraints - Tatiane Del Arco Franzotti; Maurício Ribeiro do Valle (BBR: Brazilian Business Review)
The purpose of this paper is to investigate the impacts of financial crises on investments and financing of constrained and unconstrained Brazilian firms, specifically analyzing the impact of the 2008 subprime crisis and the 2015 Brazilian economic crisis. For this purpose, the companies were classified as constrained or non-constrained by the criterion of the existence or non-existence of ratings, using quarterly data between Q1 2007 and Q3 2016, and adopting the panel analysis as the method. The results indicate that only the Brazilian crisis of 2015 had a negative impact on corporate investments, with this impact being greater on constrained firms, with evidence that cash was more relevant to these firms. Regarding the impact of crises on leverage, the 2008 subprime crisis showed a greater negative impact on the leverage of constrained firms, accompanied by an increase in the proportion of short-term debt, mainly to these companies.